1969
DOI: 10.12669/pjms.321.8758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pan Retinal Photocoagulation on Central Macular Thickness and Visual Acuity in Proliferative Diabetic Retinopathy

Abstract: Objective:To evaluate the effect of pan-retinal photocoagulation with Pattern Scan Laser (pascal)on best corrected visual acuity and central macular thickness in patients having proliferative diabetic retinopathy (PDR).Methods:This study was conducted at AFIO, Rawalpindi, Pakistan from Oct 2014 to Jul 2015. Sixty seven eyes of 46 patients having proliferative diabetic retinopathy were included in the study. All patients underwent ophthalmic clinical examination including uncorrected distant visual acuity (UCVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
4
7
0
1
Order By: Relevance
“…Alagozetal C demonstrated in their study that in VH secondary to PDR IVB reduces requirement for surgery and increases the number of patients in which PRP could have applied in early period but no impact on vision. 20 , 21 Whereas in our study we found a better visual outcome with PRP plus group.…”
Section: Discussionsupporting
confidence: 41%
“…Alagozetal C demonstrated in their study that in VH secondary to PDR IVB reduces requirement for surgery and increases the number of patients in which PRP could have applied in early period but no impact on vision. 20 , 21 Whereas in our study we found a better visual outcome with PRP plus group.…”
Section: Discussionsupporting
confidence: 41%
“…On the other hand laser photocoagulation has been used in the treatment of PDR for the last couple of decades and the proposed mechanism is decreasing ischemic drive, converting ischemic to anoxic retina and therefore, leading to regression of retinal new vessels. The recent use of Pattern scan laser (PASCAL) which has a short pulse duration has shown beneficial effect on DME when used for combined presentation of PDR with DME 5,6,12,18,19…”
Section: Discussionmentioning
confidence: 99%
“…Some authors claim, PRP alone with short pulse lasers can not only treat PDR but also significantly reduce the DME 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Dow Medical University study reported visual acuity improvement in 40.2% (147) eyes, deterioration in 36.9% (183) 16. Study from Armed Forces Institute of ophthalmology Rawalpindi17 concluded that Laser PRP with Pattern scan laser is safe and effective in patients with combined presentation of PDR and DME. Present study has shown that laser therapy alone is quite effective in CSME.…”
Section: Discussionmentioning
confidence: 99%
“…This makes laser application still the treatment of choice in CSME and PDR when affordability and follow up is always a problem. Several national studies have shown effectivity of laser therapy in PDR 15-17. This study, intends to see effectivity of laser therapy in CSME.…”
Section: Introductionmentioning
confidence: 89%